El significado de la Constitución en el programa político de Agustín de Iturbide, 1821-1824 - Arenal Fenochio, Jaime del (El Colegio de México, A.C., 1998)
One of the most widespread interpretations of Agustín de lturbide's consummation of the Mexican lndependence considers the political program of the Plan de Iguala and the Tratados de Córdoba as an anticonstitutional movement, opposed to the legal-political modernity prevailing in the early nineteenth century. This article seeks to discard definitively this interpretation, demonstrating that although Iturbide's political program was contrary to the Constitution of Cádiz, this was not because it was a constitution, but because it ignored the Mexican reality, always defending the need to establish a modern constitutional order for  the emerging Mexican Empire, but with an advantage over the one  from Cádiz, in that it was an order ad hoc to  the  circumstances, needs and  history of  that Empire, formerly New Spain. If Iturbide's program opposed the  1812 Spanish Constitution, it was because it privileged the historical constitution over the one accepted in Cádiz for all the Spanish Empire, not specifically for México. The author analyzes several of Iturbide's documents where  this program was expressed without contradictions from 1821 to the moment of his death in 1824.